Computed Tomography Pulmonary Vascular Volume Ratio Can Be Used to Evaluate the Effectiveness of Pulmonary Angioplasty in Peripheral Pulmonary Artery Stenosis - Goo, Hyun Woo (Korean J Radiol, 2019)
OBJECTIVE: To explore whether computed tomography (CT) pulmonary vascular volume ratio can be used to evaluate the effectiveness of pulmonary artery angioplasty in patients with peripheral pulmonary artery stenosis. MATERIALS AND METHODS: Changes in CT pulmonary vascular volume ratio between serial cardiothoracic CT examinations were calculated in 38 patients. Fifteen patients underwent interim pulmonary artery angioplasty (group 1), while 23 did not (group 2). According to the effectiveness of pulmonary artery angioplasty, patients in group 1 were further divided into group 1A (improved or aggravated) and group 1B (ineffective). Changes in the pulmonary vascular volume percentages among the three groups (group 1A, group 1B, and group 2) on serial CT examinations were compared. RESULTS: Pulmonary artery angioplasty on serial CT examinations was successful in seven patients, ineffective in seven patients, and aggravated in one patient. As a result, eight patients were included in group 1A and seven were included in group 1B. Changes in the CT pulmonary vascular volume percentages in group 1A were statistically significantly greater than those in group 1B (11.6 ± 5.6% vs. 2.7 ± 1.6%, p < 0.003) and group 2 (11.6 ± 5.6% vs. 1.9 ± 1.4%, p < 0.002), while no statistically significant difference was found between group 1B and group 2 (2.7 ± 1.6% vs. 1.9 ± 1.4%, p > 0.1). CONCLUSION: CT pulmonary vascular volume ratio can be used to evaluate the effectiveness of pulmonary artery angioplasty in patients with peripheral pulmonary artery stenosis.